Exploring the Role of Emergency Funds, Insurance Ownership, and Retirement Planning in the Financial Well-Being of Indonesian Millennials - Pwee Leng; Graceline Melinda (Jurnal Akuntansi dan Keuangan, 2025)
This study investigates the influence of retirement planning, insurance ownership, and emergency funds on the financial well-being of millennials in Indonesia. Using a quantitative associative approach, data were collected via an online questionnaire from 159 Indonesian millennials aged 29–44. Emergency funds and insurance ownership significantly influenced financial well-being, while retirement planning showed no significant impact. The results show the importance of adopting comprehensive financial planning approaches to strengthen millennials’ financial resilience and confidence. The study contributes empirically by combining the three variables into a single contextual framework within a developing country. Practical implications include the need to improve financial literacy, promote insurance awareness, and foster emergency saving behavior. Future studies are encouraged to investigate other potential determinants, such as social influences or the adoption of fintech services, and to consider employing qualitative or mixed-method approaches to obtain a more comprehensive understanding of millennial financial behavior.